A Participatory GIS Framework for Multi-Hazard Climate Risk Mapping in Indonesia - Trida Ridho Fariz; Ratna Budiarti; Jassica Listyarini; Atikah Tri Puspitasari; Nadia Calysta; Muhammad Ahganiya Naufal; Andhina Putri Heriyanti; Norma Eralita (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
Climate change has emerged as a global crisis with severe consequences for tropical and coastal regions. Pekalongan Regency, Indonesia, exemplifies these challenges, facing recurrent floods and landslides that threaten livelihoods and infrastructure. Risk mapping is urgently needed to guide adaptation strategies, yet many regions face constraints due to limited data availability. This study develops a multi-hazard risk mapping approach that integrates Geographic Information System (GIS) technology with stakeholder participation through Public Participation GIS (PPGIS). Hazard and vulnerability analyses were conducted using disaster records, socio-economic indicators, and spatial datasets, validated through Focus Group Discussions (FGDs) with government agencies and local stakeholders. The findings were synthesized into a structured four-stage framework encompassing stakeholder education (Kick-off), preliminary spatial analysis, participatory indicator validation, and finalization of risk maps. Results reveal distinct spatial patterns: flood risks dominate northern coastal and riverine villages, while landslide hazards are concentrated in the southern highlands. Stakeholder involvement not only improved data validity but also enhanced local adaptive capacity. The proposed PPGIS framework provides a transferable model for participatory climate resilience planning, particularly in data-scarce regions such as the global south area.